Development Of Education In Palembang In 1942-1950 (Contribution Of Learning Materials For The Course Of History Of Education) - Pandu Wiranata; Sani Safitri; Alian Alian (Criksetra: Jurnal Pendidikan Sejarah, 2018)
This research entitled "Development of Education in Palembang In Year 1942-1950" The problems in this research is How Education in Palembang in 1942-1950 and How Development of Education in Palembang in 1942-1950. In accordance with the problem the purpose of this study is intended to know more clearly how the education in Palembang in 1942-1950, and how the development of education at the time. The methodology used in this study is the historical method. From the results of this study it is found that the education that opened in Palembang in the Japanese period is not much, where the schools in the Netherlands that the number is not sufficient by the Japanese increasingly reduced, because the military government of Japan gave little attention to education in this area when compared with Java. The schools that existed during the occupation of the Japanese army were organized by the Japanese government and organized by private bodies such as Taman Siswa, Muhammadiyah, Methodist (Zending), Catholic (Mission) and local religious scholars. In the Japanese era Zending and Mission schools were forced to close, as Methodist schools used the English language of instruction, while the Catholic schools of teachers were mostly Dutch. In general, education in early independence is strived to match and approach the education system in developed countries. During the transition between 1945-1950, South Sumatra experienced difficulties in both socioeconomic, political and cultural fields, including education. Of the number of school-age children only a few percent who can enjoy the school, so the remaining 90% of the population of South Sumatra, especially Palembang are still many who are illiterate.